Kingdom of the Netherlands-Aruba : 2021 Article IV Consultation Discussions-Press Release; Staff Report; and Staff Supplement. (IMF Staff Country Reports; Country Report ;, 2021)
Aruba managed to contain the pandemic in the first months of the outbreak but experienced a resurgence of new infections in the summer. The economic impact of COVID-19 is particularly severe given Aruba's high dependency on tourism. While the authorities' swift response has helped contain the human and economic damage, it could not avoid a severe GDP contraction.